Temperature Measurement during Millisecond Annealing Ripple Pyrometry for Flash Lamp Annealers - Reichel, Denise (MatWerk, 2015)
Denise Reichel studies the delicate subject of temperature measurement during lamp-based annealing of semiconductors, in particular during flash lamp annealing. The approach of background-correction using amplitude-modulated light to obtain the sample reflectivity is reinvented from rapid thermal annealing to apply to millisecond annealing. The author presents a new method independent of the lamp operation to obtain this amplitude modulation and derives a formula to describe the process. Further, she investigates the variables of the formula in depth to validate the method's suitability for background-corrected temperature measurement. The experimental results finally proof its power for elevated temperatures. Contents Fundamentals of flash lamp annealing of shallow Boron-doped Silicon Fundamentals of surface temperature measurements during flash lamp annealing Concept of ripple pyrometry during flash lamp annealing      Ripple pyrometry for flash lamp annealing - Experiments Target Groups ·Researchers and students from the fields of materials sciences and physics ·Practitioners from microelectronics and photovoltaics industry About the Author Dr. Denise Reichel currently works in technical sales and consulting for temperature  measurement needs and as a lecturer for thermodynamics and heat and mass transfer.  .